The usage intention of chatbot technology in hospitality and tourism industry: customers’ perspective / Norzuwana Sumarjan ... [et al.] - Sumarjan, Norzuwana; Mazlan, Nurfatihah; Saiful Azmi, Nur Shuhada; Kamaruddin, Muhammad Abid; Salleh, Aqilah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Chatbot technology is used as part of an excellent tool to enhance communication, boost the efficiency of service delivery, save costs, and enhance customers’ experience. Nevertheless, the usage of chatbot is still low in Malaysia’s hospitality and tourism industry. Therefore, this study aims to examine the usage intention of chatbot technology in the hospitality and tourism industry focusing on communication accuracy, customization, and anthropomorphism. The moderating role of technology anxiety was also observed. A total of 103 online were obtained via questionnaires, distributed among hospitality and tourism consumers who are aware about chatbot technology. A purposive sampling technique was used. Data were analysed using multiple regression and PROCESS MACRO by Hayes to test the hypotheses. The results established the relationship between communication accuracy, customization, anthropomorphism, and usage intention of chatbot technology. Nevertheless, technology anxiety does not moderate the relationship between communication accuracy, customization, anthropomorphism, and usage intention of chatbot technology. It is hoped that this study could help the chatbot providers to better understand the benefits of chatbot and factors affecting chatbot usage intention, thus pique and improve customers’ interest in utilizing chatbot.